anonymous
  • anonymous
Herlp Mer Irn Marth!!!
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Use the functions f(x) = 5x − 12 and g(x) = 11x + 2 to complete the function operations listed below. Part A: Find (f + g)(x). Show your work. (3 points) Part B: Find (f ⋅ g)(x). Show your work. (3 points) Part C: Find f[g(x)]. Show your work. (4 points)
anonymous
  • anonymous
@emmigrace222 @welshfella @Wxlfz @campbell_st @mathstudent55 @Michele_Laino
welshfella
  • welshfella
A just add 5x - 12 and 11x + 2

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

welshfella
  • welshfella
B 5x - 12 - (11x + 2) be careful of the signs when you deal with the parentheses
anonymous
  • anonymous
Part A: (f + g)(x) = 16x - 10 Add x Terms: (f + g)(x) = 11x + 5x = 16x Add Regular Terms: (f + g)(x) = -12 + 2 = 10 Solution: (f + g)(x) = 16x - 10
anonymous
  • anonymous
So, part b I just multiply them? @campbell_st ?
anonymous
  • anonymous
Part A: (f * g)(x) = 16x - 10 Multiply x Terms: (f * g)(x) = 11x * 5x = 55x Multiply Regular Terms: (f * g)(x) = -12 * 2 = 24 Solution: (f + g)(x) = 55x - 24
anonymous
  • anonymous
What is C then @welshfella ?
welshfella
  • welshfella
your first post where you worked out f + g was correct A is 16x - 10
welshfella
  • welshfella
Oh part B is multiplying Sorry i misread the question
anonymous
  • anonymous
Ok, cool. So, what is Part C?
welshfella
  • welshfella
(f ⋅ g)(x) = (5x -12)(11x + 2) = 5x(11x + 2) - 12(11x + 2) = 55x^2 + 10x - 132x - 24 = 55x^2 - 122x - 24
welshfella
  • welshfella
C you replace the x in f(x) by g(x) then simplify |dw:1438287486460:dw|
welshfella
  • welshfella
f(g(x)) = 5 (11x + 2) - 12 simplify
anonymous
  • anonymous
Part C: f[g(x)] = 55x^2 - 122x - 24 Group Into Two: f[g(x)] = (5x -12)(11x + 2) = Replace f(x) and g(x): f[g(x)] = 5x(11x + 2) - 12(11x + 2) Simplify: f[g(x)] = 55x^2 + 10x - 132x - 24 Solution: f[g(x)] = 55x^2 - 122x - 24
anonymous
  • anonymous
@welshfella

Looking for something else?

Not the answer you are looking for? Search for more explanations.